Effect of Moisture on the Macro Failure Characteristics of Weakly Consolidated Mudstone: Mesomechanism - Jiahui Xu; Guichen Li; Haoyu Rong; Mohamed Elgharib Gomah; Changlun Sun; Jinghua Li; Suhui Zhang (Geofluids)
Mudstone, whose significant characteristic is water-weakening, widely exists in all kinds of geotechnical engineering, which brings great security risks to engineering safety. In this paper, through a series of macro and meso test methods, the macro and meso action mechanism of water on the weakly consolidated plane of mudstone was studied. In the uniaxial compressive strength test, the mudstone cementation plane was the main part of the fracture derived. Under the moist state, the strength of mudstone would decrease significantly, which was inversely correlated with relative moisture content. In the case of flooding, mudstone cracking occurred only along the cementation plane. Through ESEM+mapping test, results showed the humidification curing caused obvious damage to the cemented plane, where sodium and calcium were lost without a certain cause. The cemented plane was rich in kinds of clay minerals in mesoscale and presented an inhomogeneous state. The surface hardness data obtained from nanoindentation were discrete and difficult to quantitatively evaluate the mesomechanical properties. However, compared with the dry state, the data set of the moist state had a significant decline, showing a weakening effect. The mudstone is prone to fail along these weakly consolidated planes. Moisture intrudes into the bedding plane further deteriorating their consolidation.